Secular changes in shuttle-run performance: A 23-year retrospective comparison of 9- to 11-year-old children - Reed, K. E.; Warburton, D. E. R.; Whitney, C. L.; McKay, H. A. (Pediatric Exercise Science, 2006)
Low physical fitness is associated with increased risk of cardiovascular disease (CVD) in adults and a higher incidence of CVD risk factors in children. Our aim was to compare the aerobic performance of Canadian children in 2004 with that of children measured 2 decades ago. We conducted a cross-sectional comparison of 2 data sets: (a) a 2004 cohort (n = 252) and (b) data from Leger`s 1981 cohort (n = 2,151). Performance was assessed using Leger`s 20 m Shuttle Run Test. First, we compared VO2max by cohort (in age and sex subgroups). Second, we used 1981 derived data, to re-create the original distribution curves, then calculated a 1981 equivalent percentile for each 2004 cohort child. We found that aerobic performance was lower at all ages in 2004 compared with 1981 (p < .01). Thus, the 50th percentile for fitness of children in 2004 was equivalent to that of children in the lowest 20% of fitness in 1981. We support the view that the performance of children on aerobic fitness tests is declining.